2010
DOI: 10.2340/16501977-0524
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of exercise on work disability in patients with non-acute non-specific low back pain: Systematic review and meta-analysis of randomised controlled trials

Abstract: Exercise interventions have a significant effect on work disability in patients with non-acute non-specific low back pain in the long term. No conclusions can be made regarding exercise types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 48 publications
(2 reference statements)
2
49
0
5
Order By: Relevance
“…There is indeed abundant evidence suggesting the benefits of therapeutic exercise on pain and disability in patients with chronic non-specific LBP. 9,10,11,12 In spite of the therapeutic gains from exercises, findings from a systematic review concluded that the most effective mode of exercise therapy remain debatable. 11 This conclusion has stimulated scientific curiosity to evaluate the relative efficacy of the modes of exercise therapy in physiotherapy practice.…”
Section: Introductionmentioning
confidence: 99%
“…There is indeed abundant evidence suggesting the benefits of therapeutic exercise on pain and disability in patients with chronic non-specific LBP. 9,10,11,12 In spite of the therapeutic gains from exercises, findings from a systematic review concluded that the most effective mode of exercise therapy remain debatable. 11 This conclusion has stimulated scientific curiosity to evaluate the relative efficacy of the modes of exercise therapy in physiotherapy practice.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the growing body of evidence demonstrating the benefits of physical activity, including decreasing both obesity-associated morbidity and mortality [29][30] and disability from chronic musculoskeletal pain [31], OIF/OEF veterans using the VA are an ideal population for interventions centered around increasing physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Ono što je zajedničko je dobar kratkotrajni i loš dugotrajni terapijski efekat 4,5,[7][8][9][10] . Zajednički terapijski učinak za sve studije je oko 9%…”
Section: Diskusijaunclassified